a, Thay x=2 vào A(x) ta có:
\(x^2-2x=\left(-2\right)^2-2.\left(-2\right)=4-\left(-4\right)=8\)
\(b,A\left(x\right)=x^2-2x=0\\ \Leftrightarrow x\left(x-2\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=0\\x-2=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=0\\x=2\end{matrix}\right.\)
a: \(A\left(-2\right)=\left(-2\right)^2-2\cdot\left(-2\right)=8\)
b: Đặt A(x)=0
=>x(x-2)=0
=>x=0 hoặc x=2
a, Ta có \(A\left(-2\right)=4-2\left(-2\right)=4+4=8\)
b, \(A\left(x\right)=x^2-2x=0\Leftrightarrow x\left(x-2\right)=0\Leftrightarrow x=0;x=2\)